2022
DOI: 10.1002/aenm.202201614
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Strategy for Highly Efficient and Super Flexible Thick‐film Organic Solar Cells

Abstract: Efficient organic solar cells (OSCs) equipped with thick‐film active layers and high flexibility are of great significance for industrial preparation and practical applications. Herein, a ternary strategy coupled with a functional additive is employed to obtain efficient thick‐film flexible OSCs. A novel polymer donor PBB1‐F with good planarity is synthesized as a third component to optimize photon capture and molecular stacking. Meanwhile, a high dielectric constant polyarene ether (PAE) functional additive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 62 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…Then crack-onset-strain (COS) as another important figureof-merit for all-polymer blend is evaluated, which represents the film ductility. [42][43][44][45][46][47] As presented in Figure 1d and Table S1 (Supporting Information), the strain-stress curves of all-polymer blends are presented in Figure 2d and their derived COS and mechanical toughness values are listed in Table S1 (Supporting Information). It was found that the proper addition of PTQ10 could significantly boost the ductility of active layers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Then crack-onset-strain (COS) as another important figureof-merit for all-polymer blend is evaluated, which represents the film ductility. [42][43][44][45][46][47] As presented in Figure 1d and Table S1 (Supporting Information), the strain-stress curves of all-polymer blends are presented in Figure 2d and their derived COS and mechanical toughness values are listed in Table S1 (Supporting Information). It was found that the proper addition of PTQ10 could significantly boost the ductility of active layers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, improved morphology can give better charge transport and lower carrier recombination, which further explains the phenomenon of the higher J SC in the ternary OSC. In addition, the high dielectric constant PFBEK is added to regulate the phase separation, crystallinity, and electric field of the ternary device, , which can further increase the photovoltaic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the exciton diffusion can be further improved by texturing the intermolecular interaction in mixed NFAs, , enabling efficient light-to-electricity conversion in ternary systems. Thick active layers can be applied in NFA-based devices with PCEs largely retained toward practical applications. …”
Section: Device Implicationmentioning
confidence: 99%